Wear-resistant rare earth magnesium alloy composite material and preparation method thereof

By setting a transition layer and a wear-resistant layer on the magnesium alloy matrix and utilizing a combination of modified tungsten carbide and rare earth composites, the problem of insufficient wear resistance and corrosion resistance of magnesium alloys is solved, and the material's high wear resistance and corrosion resistance are achieved, making it suitable for aerospace, automobile manufacturing, and electronics fields.

CN120700487APending Publication Date: 2025-09-26SHENZHEN ESTHER NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510983650.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Magnesium alloys have poor wear resistance and corrosion resistance, which limits their application in some working conditions with high surface performance requirements. Existing preparation methods have problems such as poor bonding or thermal stress affecting material properties.

Method used

A transition layer and a wear-resistant layer are set on the magnesium alloy substrate. The wear-resistant layer is composed of modified tungsten carbide particles, rare earth composites and nickel-based alloy powder. Laser cladding and surfacing technology are used to achieve a good combination of the substrate and the wear-resistant layer. Modified tungsten carbide and rare earth composites are used to improve the wear resistance and corrosion resistance of the material.

Benefits of technology

The wear resistance, corrosion resistance and service life of magnesium alloy composite materials are significantly improved. The transition layer relieves the stress caused by the difference in thermal expansion coefficient, enhances the overall structural stability of the material, and is easy to mass industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005503689840000101
    Figure BDA0005503689840000101
  • Figure BDA0005503689840000111
    Figure BDA0005503689840000111
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium alloy materials, in particular to a wear-resistant rare earth magnesium alloy composite material and a preparation method thereof.The composite material sequentially comprises a magnesium alloy matrix layer, a transition layer and a wear-resistant layer, and the wear-resistant layer comprises, by weight, 20-25 parts of modified tungsten carbide particles, 6-10 parts of a rare earth compound and 65-70 parts of nickel-based alloy powder; according to the composite material, the transition layer and the wear-resistant layer are arranged on the magnesium alloy matrix, so that good combination between the matrix and the wear-resistant layer is realized, meanwhile, the wear resistance and the corrosion resistance of the material are remarkably improved, and the service life of the material is remarkably prolonged. The preparation method is convenient to operate, easy to control and convenient for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to a wear-resistant rare earth magnesium alloy composite material and a preparation method thereof. Background Art

[0002] Magnesium alloys are widely used in aerospace, automotive, electronics, and other fields due to their low density, high specific strength, and excellent shock absorption properties. However, their poor wear and corrosion resistance limits their application in applications requiring high surface properties. To overcome this problem, researchers are committed to developing high-performance, wear-resistant composite materials to improve the service life and reliability of magnesium alloys.

[0003] Currently, common methods for preparing wear-resistant composite materials include surface coating and cladding techniques. However, these methods have limitations. For example, traditional surface coating techniques often struggle to achieve a good bond between the coating and the substrate, resulting in the coating easily falling off during use. While cladding techniques can improve the material's wear resistance, they can easily introduce significant thermal stress, affecting the material's overall performance.

[0004] When magnesium alloys are used as moving parts, they need to have not only good corrosion resistance, but more importantly, their surface should have good comprehensive friction properties, including good wear resistance, lubrication and friction reduction. The film layer formed by magnesium alloys during micro-arc oxidation has high hardness and good wear resistance, but it has a high friction coefficient and poor lubrication and friction reduction ability. At the same time, the wear life is also short, and the comprehensive friction performance is significantly poor. Therefore, there is an urgent need for a magnesium alloy composite material with good wear resistance, good corrosion resistance and good mechanical properties. Summary of the Invention

[0005] To address these issues, the present invention provides a wear-resistant rare earth magnesium alloy composite material and a method for preparing the same. By providing a transition layer and a wear-resistant layer on a magnesium alloy substrate, a good bond between the substrate and the wear-resistant layer is achieved, significantly improving the material's wear resistance, corrosion resistance, and service life. The preparation method is easy to operate and control, facilitating large-scale industrial production.

[0006] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are:

[0007] A wear-resistant rare earth magnesium alloy composite material, comprising a magnesium alloy matrix layer, a transition layer, and a wear-resistant layer in sequence, wherein the wear-resistant layer comprises, by weight, 20 to 25 parts of modified tungsten carbide particles, 6 to 10 parts of a rare earth compound, and 65 to 70 parts of a nickel-based alloy powder;

[0008] The preparation method of the modified tungsten carbide particles comprises the following steps:

[0009] Step 1, tungsten carbide surface activation treatment: immerse the tungsten carbide powder in a mixed acid solution, ultrasonically treat at 70-75°C for 25-35 minutes, then wash and dry;

[0010] Step 2: Place the activated tungsten carbide into a fluidized bed reactor, evacuate to 10-2Pa, introduce reaction gas, which is titanium tetrachloride, nitrogen and hydrogen, and deposit at 890-910°C for 40-50 minutes to obtain tungsten carbide composite particles;

[0011] Step 3: The tungsten carbide composite particles are subjected to vacuum degassing pretreatment at a temperature of 240-260°C for 25-35 minutes under vacuum conditions, and then filled with argon to normal pressure, followed by introduction of argon-hydrogen mixed gas, at a power of 2.8-3.2kW and a temperature of 290-310°C, for plasma reduction for 35-45 minutes.

[0012] Preferably, in step 1, the mixed acid solution comprises phosphoric acid, nitric acid and deionized water in a volume ratio of 12-16:8-12:70-80, the concentration of phosphoric acid is 85%, the concentration of nitric acid is 65%, and the weight-to-volume ratio of the tungsten carbide powder to the mixed acid solution is 1 g:7-9 ml.

[0013] Preferably, in step 2, the flow rates of the reaction gases are: titanium tetrachloride 48-52 ml / min, nitrogen 550-600 ml / min, and hydrogen 290-310 ml / min.

[0014] Preferably, in step 3, the volume percentage of hydrogen in the argon-hydrogen mixed gas is 3%.

[0015] Preferably, the method for preparing the rare earth composite comprises the following steps:

[0016] Step S1, spray pyrolysis synthesis: yttrium nitrate, aluminum nitrate, and citric acid are dissolved in a mixed solvent of ethanol and water to obtain a precursor solution, and spray pyrolysis reaction is carried out under a nitrogen atmosphere with nitrogen carrier gas at a flow rate of 25 to 30 L / min, an inlet temperature of 300° C., a reaction zone temperature of 1280-1320° C., an atomization pressure of 0.3 MPa, and a residence time of 2 to 2.5 seconds to obtain spherical particles;

[0017] Step S2, placing the spherical particles into a plasma reactor, introducing a mixed gas of hexafluoroethane and argon at a pressure of 18-22 Pa, a power of 280-320 W, and a temperature of 140-160° C. for 8-12 minutes to form a fluorinated layer;

[0018] Step S3, perfluorodecyltrimethoxysilane and hexane are mixed to obtain a mixed solution, triethylamine is added, and then the fluorinated spherical particles are added to the above solution, reacted at 35-45° C. in a dry nitrogen atmosphere for 4-6 hours, and post-treated to obtain the product.

[0019] Preferably, in step S1, in the precursor solution, yttrium nitrate is Y(NO3)3·6H2O with a concentration of 0.8 mol / L, aluminum nitrate is Al(NO3)3·9H2O with a concentration of 2.0 mol / L, the concentration of citric acid is 1.2 mol / L, and the volume ratio of deionized water and ethanol in the solvent is 1:1.

[0020] Preferably, in step S2, the volume ratio of hexafluoroethane to argon in the mixed gas of hexafluoroethane and argon is 2:2.8-3.2.

[0021] Preferably, in step S3, the concentration of perfluorodecyltrimethoxysilane in the mixed solution is 1% to 2%, the amount of triethylamine added is 0.1% of the mixed solution, and the weight ratio of the fluorinated spherical particles to perfluorodecyltrimethoxysilane is 100:1-2.

[0022] The preparation method of the wear-resistant rare earth magnesium alloy composite material is as follows: after mixing the raw materials for the wear-resistant layer, cladding is performed under argon protection at a laser power of 2.0-2.8kW, a scanning speed of 3.3-3.7mm / s.

[0023] Preferably, the transition layer raw materials include 25 to 35 parts of rare earth compound and 65 to 75 parts of magnesium yttrium alloy in parts by weight, and are prepared by surfacing welding with a current of 130 to 150 A, a scanning speed of 2.5 to 3.5 mm / s, a powder feeding rate of 16 to 19 g / min, and are carried out under the protection of a mixed gas of argon and hydrogen, with a volume ratio of Ar to H2 of 97:3 and a flow rate of 10 to 14 L / min.

[0024] The present invention has the following beneficial effects:

[0025] The wear-resistant rare earth magnesium alloy composite material of the present invention achieves a good bond between the substrate and the wear-resistant layer by providing a transition layer and a wear-resistant layer on the magnesium alloy substrate, significantly improving the material's wear resistance, corrosion resistance, and service life. The transition layer acts as a buffer and transition, reducing stress caused by the difference in thermal expansion coefficient between the substrate and the wear-resistant layer, and enhancing the overall structural stability of the composite material.

[0026] The wear-resistant layer of the present invention uses Ni60A as a bonding phase, which wraps hard particles after melting; rare earth compounds are dispersed at the grain boundaries of Ni60A to refine the grains; modified WC provides the main wear-resistant skeleton, and the TiN layer wears preferentially but peels off slowly during the friction process, achieving self-lubrication. Among them, the modified tungsten carbide undergoes surface activation treatment (step 1) to form a clean and activated tungsten carbide surface, which improves the subsequent TiN deposition bonding force. Step 2 forms a TiN ceramic layer, whose thermal expansion coefficient is close to that of tungsten carbide, avoiding interfacial stress cracking; and the TiN layer blocks oxygen diffusion, improving the high-temperature oxidation resistance of tungsten carbide. The third step is plasma reduction, which reduces the TiN surface oxide, removes surface impurities, forms nano-scale roughness, reduces the surface energy of the TiN layer, significantly improves wettability with Ni60A, and can also inhibit the agglomeration of tungsten carbide particles during laser cladding, achieving uniform dispersion. The rare earth composite material first uses citric acid to chelate metal ions and then undergoes high-temperature pyrolysis to obtain spherical particles with good fluidity. Then, plasma fluorination is performed to form a composite fluoride layer, which fills surface defects in the spherical particles. The fluoride layer reduces surface energy and inhibits the reaction between the spherical particles and the magnesium matrix during cladding. Finally, in step S3, the long fluorocarbon chains form a hydrophobic film, blocking water and oxygen corrosion. Si—O—Y covalent bonds enhance interfacial bonding, improving the dispersion stability of the spherical rare earth composite particles in Ni60A.

[0027] Furthermore, in the wear-resistant layer, the modified WC bears the primary responsibility for abrasive wear, while the TiN layer slows WC oxidation. Under the action of frictional heat, the surface fluorine-carbon chains of the rare earth composite decompose to form fluorides, which form a tribochemical reaction film with the TiN, reducing the friction coefficient and wear rate. The rare earth composite inhibits the migration of Ni60A grain boundaries, while the TiN layer blocks the carbon diffusion of WC at high temperatures, preventing the formation of brittle phases (such as M6C), and together they increase the hardness of the composite material. During the cladding process, the silane layer of the rare earth composite pyrolyzes to form active SiO2, which reacts with the TiN layer to enhance the interfacial bonding between WC and Ni60A.

[0028] The Y element of the magnesium-yttrium alloy in the transition layer dissolves in the magnesium matrix, forming a solid solution strengthening that reduces the transition layer's thermal expansion coefficient, while the rare earth composite particles enhance its resistance to plastic deformation. The transition layer's composition and structure lie between those of the magnesium alloy matrix and the wear-resistant layer. This significantly reduces the difference in thermal expansion coefficients between the matrix, transition layer, and wear-resistant layer, lowering thermal stress and minimizing the generation and propagation of cracks. The transition layer exhibits good chemical and physical compatibility with the magnesium alloy matrix and wear-resistant layer, enhancing the overall bonding strength of the composite material and ensuring that the wear-resistant layer does not fall off during use. Overlay welding ensures low heat input to prevent overburning of the magnesium matrix; the H2 in the Ar / H2 mixture (97:3) reduces interfacial oxides, enhancing bonding strength.

[0029] The preparation method of the present invention is easy to operate and control, making it suitable for large-scale industrial production. Gradient annealing can optimize the material's internal microstructure and reduce internal stress, while shot peening can increase the material's surface hardness and fatigue resistance. The combination of the two can simultaneously improve the material's internal and surface properties, reduce crack initiation and propagation, and enhance the material's fatigue resistance and wear resistance. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0031] Alloy steel shot (Φ0.3mm) was from Zibo Daya Metal Technology Co., Ltd.; magnesium-yttrium alloy, MgY20, was from Hunan Hengbo New Materials Co., Ltd.; nickel-based alloy powder was Ni60A, was from Qinghe County Yinghe Metal Materials Co., Ltd.; yttrium nitrate was Y(NO3)3·6H2O; aluminum nitrate was Al(NO3)3·9H2O; benzotriazole, 99.8% content, was from Jinan Jiewei Chemical Technology Co., Ltd.; the raw materials used in the following examples were all common commercially available products.

[0032] Example 1

[0033] A wear-resistant rare earth magnesium alloy composite material, comprising a magnesium alloy matrix layer, a transition layer, and a wear-resistant layer in sequence, wherein the wear-resistant layer comprises, by weight, 23 parts of modified tungsten carbide particles, 8 parts of a rare earth compound, and 68 parts of a nickel-based alloy powder;

[0034] The preparation method of the modified tungsten carbide particles comprises the following steps:

[0035] Step 1, tungsten carbide surface activation treatment: immerse the tungsten carbide powder in a mixed acid solution, ultrasonically treat it at 72°C for 30 minutes, and the frequency is 40kHz. Wash it with deionized water until it is neutral, and vacuum dry it at 120°C for 1 hour. The mixed acid solution includes phosphoric acid, nitric acid, and deionized water. The volume ratio of the three is 14:10:75, the concentration of the phosphoric acid is 85%, and the concentration of the nitric acid is 65%. The weight volume ratio of the tungsten carbide powder to the mixed acid solution is 1g:8ml;

[0036] Step 2: Fluidized bed chemical vapor deposition of titanium nitride: The activated tungsten carbide powder is loaded into a fluidized bed reactor, evacuated to 10-2 Pa, and reactant gases of titanium tetrachloride, nitrogen, and hydrogen are introduced. The reaction is deposited at 900°C for 45 minutes to obtain tungsten carbide composite particles. The flow rates of the reactant gases are 50 ml / min for titanium tetrachloride, 570 ml / min for nitrogen, and 300 ml / min for hydrogen, respectively.

[0037] Step 3: Plasma reduction: Vacuum degassing pretreatment: Place the tungsten carbide composite particles in a vacuum furnace and evacuate to 10 - 2Pa, temperature 250°C, keep warm for 30 minutes to remove the adsorbed gas, then fill the furnace with high-purity argon to normal pressure, repeat 3 times (argon purity ≥ 99.999%) for inert gas replacement, then introduce argon-hydrogen mixture, power 3.0kW, temperature 300°C, and carry out plasma reduction treatment for 40 minutes. The volume percentage of hydrogen in the argon-hydrogen mixture is 3%.

[0038] The method for preparing the rare earth composite comprises the following steps:

[0039] Step S1, spray pyrolysis synthesis: yttrium nitrate, aluminum nitrate, and citric acid are dissolved in a mixed solvent of ethanol and water to obtain a precursor solution, and spray pyrolysis reaction is carried out under a nitrogen atmosphere, with nitrogen carrier gas, a flow rate of 28 L / min, an inlet temperature of 300°C, a reaction zone temperature of 1300°C, an atomization pressure of 0.3 MPa, and a residence time of 2.3 seconds to obtain spherical particles; wherein, in the precursor solution, yttrium nitrate is Y(NO3)3·6H2O with a concentration of 0.8 mol / L, aluminum nitrate is Al(NO3)3·9H2O with a concentration of 2.0 mol / L, and the concentration of citric acid is 1.2 mol / L, and the volume ratio of deionized water to ethanol in the solvent is 1:1;

[0040] Step S2, placing the spherical particles into a plasma reactor, introducing a mixed gas of hexafluoroethane and argon at a pressure of 20 Pa, a power of 300 W, and a temperature of 150° C. for 10 minutes to form a fluorinated layer; wherein the volume ratio of hexafluoroethane to argon in the mixed gas of hexafluoroethane and argon is 2:3;

[0041] Step S3, perfluorodecyltrimethoxysilane and hexane are mixed to obtain a mixed solution, triethylamine is added, and then the fluorinated spherical particles are added to the above solution, and the mixture is reacted at 40°C, magnetically stirred at 200 rpm, and in a dry nitrogen atmosphere for 5 hours. Then, the mixture is centrifuged at 4000 rpm for 10 minutes, the particles are collected, and the particles are washed with hexane 3 times (10 ml / g particles each time) to remove the physically adsorbed perfluorodecyltrimethoxysilane, and vacuum dried at 120°C for 1.5 hours to obtain the product; in step S3, the concentration of perfluorodecyltrimethoxysilane in the mixed solution is 1.5%, the amount of triethylamine added is 0.1% of the mixed solution, and the weight ratio of the fluorinated spherical particles to perfluorodecyltrimethoxysilane is 100:1.5.

[0042] The preparation method of the above-mentioned wear-resistant rare earth magnesium alloy composite material comprises the following steps:

[0043] Step a, pre-treating the magnesium alloy substrate, specifically: using 120 mesh silicon carbide sand, air pressure 0.5 MPa, sandblasting the magnesium alloy substrate to a roughness Ra = 3.5 μm, and then pickling, soaking in a mixed acid solution at 40° C. for 90 seconds, the mixed acid solution containing 10% glacial acetic acid, 5% nitric acid (nitric acid concentration of 65%) and 0.1% benzotriazole;

[0044] Step b, preparing a transition layer: the transition layer raw materials include 30 parts by weight of a rare earth compound and 70 parts of a magnesium-yttrium alloy, which are mixed and prepared by surfacing welding, wherein the current is 140A, the scanning speed is 3mm / s, the powder feeding rate is 18g / min, and the protection is carried out under a mixed gas of argon and hydrogen, the volume ratio of Ar to H2 is 97:3, and the flow rate is 12L / min;

[0045] Step c, preparing the wear-resistant layer: after mixing the raw materials for the wear-resistant layer, cladding was performed under a laser power of 2.4 kW, a spot diameter of 2.5 mm, a scanning speed of 3.5 mm / s, and argon protection;

[0046] Step d, post-treatment; the post-treatment is first gradient annealing: 280 ° C, annealing for 1h, 380 ° C, annealing for 2h, 480 ° C annealing for 0.5h, the entire process is protected by argon, the heating rate is 10 ° C / min; then ultrasonic shot peening, using alloy shot, strength 0.25mmA, coverage 200%.

[0047] Example 2

[0048] A wear-resistant rare earth magnesium alloy composite material, comprising a magnesium alloy matrix layer, a transition layer, and a wear-resistant layer in sequence, wherein the wear-resistant layer comprises, by weight, 20 parts of modified tungsten carbide particles, 6 parts of a rare earth compound, and 70 parts of a nickel-based alloy powder;

[0049] The preparation method of the modified tungsten carbide particles comprises the following steps:

[0050] Step 1, tungsten carbide surface activation treatment: immerse the tungsten carbide powder in a mixed acid solution, ultrasonically treat it at 70°C for 35 minutes, the frequency is 35kHz, wash it with deionized water until it is neutral, and vacuum dry it at 130°C for 0.8 hours. The mixed acid solution includes phosphoric acid, nitric acid, and deionized water. The volume ratio of the three is 12:12:80, the concentration of the phosphoric acid is 85%, the concentration of the nitric acid is 65%, and the weight volume ratio of the tungsten carbide powder to the mixed acid solution is 1g:9ml;

[0051] Step 2: Fluidized bed chemical vapor deposition of titanium nitride: The activated tungsten carbide powder is loaded into a fluidized bed reactor, evacuated to 10-2 Pa, and reactant gases of titanium tetrachloride, nitrogen, and hydrogen are introduced. The reaction is deposited at 890°C for 50 minutes to obtain tungsten carbide composite particles, wherein the flow rates of the reactant gases are 52 ml / min for titanium tetrachloride, 550 ml / min for nitrogen, and 310 ml / min for hydrogen;

[0052] Step 3: Plasma reduction: Vacuum degassing pretreatment: Place the tungsten carbide composite particles in a vacuum furnace, evacuate to 10-2Pa, temperature 260°C, and keep warm for 25 minutes to remove the adsorbed gas. Then, high-purity argon is filled into the furnace to normal pressure. This is repeated 3 times (argon purity ≥ 99.999%) for inert gas replacement. Subsequently, an argon-hydrogen mixture is introduced at a power of 3.2kW and a temperature of 290°C for plasma reduction treatment for 35 minutes. The volume percentage of hydrogen in the argon-hydrogen mixture is 3%.

[0053] The method for preparing the rare earth composite comprises the following steps:

[0054] Step S1, spray pyrolysis synthesis: yttrium nitrate, aluminum nitrate, and citric acid are dissolved in a mixed solvent of ethanol and water to obtain a precursor solution, and spray pyrolysis reaction is carried out under a nitrogen atmosphere, with nitrogen carrier gas, a flow rate of 30 L / min, an inlet temperature of 300°C, a reaction zone temperature of 1280°C, an atomization pressure of 0.3 MPa, and a residence time of 2.5 seconds to obtain spherical particles; wherein, in the precursor solution, yttrium nitrate is Y(NO3)3·6H2O with a concentration of 0.8 mol / L, aluminum nitrate is Al(NO3)3·9H2O with a concentration of 2.0 mol / L, and the concentration of citric acid is 1.2 mol / L, and the volume ratio of deionized water to ethanol in the solvent is 1:1;

[0055] Step S2, placing the spherical particles into a plasma reactor, introducing a mixture of hexafluoroethane and argon at a pressure of 22 Pa, a power of 320 W, and a temperature of 140° C. for 8 minutes to form a fluorinated layer; wherein the volume ratio of hexafluoroethane to argon in the mixture of hexafluoroethane and argon is 2:3.2;

[0056] Step S3: perfluorodecyltrimethoxysilane and hexane are mixed to obtain a mixed solution, triethylamine is added, and then the fluorinated spherical particles are added to the above solution, and the mixture is reacted at 45° C., magnetic stirring at 200 rpm, and a dry nitrogen atmosphere for 4 hours. Then, the mixture is centrifuged at 4000 rpm for 10 minutes, the particles are collected, and the particles are washed with hexane three times (10 ml / g particles each time) to remove physically adsorbed perfluorodecyltrimethoxysilane, and vacuum dried at 120° C. for 1.5 hours to obtain the product. In step S3, the concentration of perfluorodecyltrimethoxysilane in the mixed solution is 1%, the amount of triethylamine added is 0.1% of the mixed solution, and the weight ratio of the fluorinated spherical particles to perfluorodecyltrimethoxysilane is 100:1.

[0057] The preparation method of the above-mentioned wear-resistant rare earth magnesium alloy composite material comprises the following steps:

[0058] Step a, pre-treating the magnesium alloy substrate, specifically: using 120 mesh silicon carbide sand, air pressure 0.5 MPa, sandblasting the magnesium alloy substrate to a roughness Ra = 3.5 μm, and then pickling, soaking in a mixed acid solution at 42° C. for 80 seconds, the mixed acid solution containing 10% glacial acetic acid, 5% nitric acid (nitric acid concentration of 65%) and 0.1% benzotriazole;

[0059] Step b, preparing a transition layer: the transition layer raw materials include 35 parts of rare earth compound and 65 parts of magnesium yttrium alloy in parts by weight, which are mixed and prepared by surfacing welding, wherein the current is 150A, the scanning speed is 2.5mm / s, the powder feeding rate is 16g / min, and the protection is carried out under a mixed gas of argon and hydrogen, the volume ratio of Ar to H2 is 97:3, and the flow rate is 10L / min;

[0060] Step c, preparing the wear-resistant layer: after mixing the raw materials for the wear-resistant layer, cladding is performed under a laser power of 2.0 kW, a spot diameter of 2.5 mm, a scanning speed of 3.6 mm / s, and argon protection;

[0061] Step d is the same as in Example 1.

[0062] Example 3

[0063] A wear-resistant rare earth magnesium alloy composite material, comprising a magnesium alloy matrix layer, a transition layer, and a wear-resistant layer in sequence, wherein the wear-resistant layer comprises, by weight, 25 parts of modified tungsten carbide particles, 10 parts of a rare earth compound, and 65 parts of a nickel-based alloy powder;

[0064] The preparation method of the modified tungsten carbide particles comprises the following steps:

[0065] Step 1, tungsten carbide surface activation treatment: immerse the tungsten carbide powder in a mixed acid solution, ultrasonically treat it at 75°C for 25 minutes, and the frequency is 45kHz. Wash it with deionized water until it is neutral, and vacuum dry it at 110°C for 1.5 hours. The mixed acid solution includes phosphoric acid, nitric acid, and deionized water. The volume ratio of the three is 16:8:70, the concentration of the phosphoric acid is 85%, and the concentration of the nitric acid is 65%. The weight volume ratio of the tungsten carbide powder to the mixed acid solution is 1g:7ml;

[0066] Step 2: Fluidized bed chemical vapor deposition of titanium nitride: The activated tungsten carbide powder is loaded into a fluidized bed reactor, evacuated to 10-2 Pa, and reactant gases of titanium tetrachloride, nitrogen, and hydrogen are introduced. The reaction is deposited at 910°C for 40 minutes to obtain tungsten carbide composite particles, wherein the flow rates of the reactant gases are 48 ml / min for titanium tetrachloride, 600 ml / min for nitrogen, and 290 ml / min for hydrogen.

[0067] Step 3: Plasma reduction: Vacuum degassing pretreatment: Place the tungsten carbide composite particles in a vacuum furnace, evacuate to 10-2Pa, temperature 240°C, and keep warm for 35 minutes to remove the adsorbed gas. Then, high-purity argon is filled into the furnace to normal pressure. This is repeated 3 times (argon purity ≥ 99.999%) for inert gas replacement. Subsequently, an argon-hydrogen mixture is introduced at a power of 2.8kW and a temperature of 310°C for plasma reduction treatment for 45 minutes. The volume percentage of hydrogen in the argon-hydrogen mixture is 3%.

[0068] The method for preparing the rare earth composite comprises the following steps:

[0069] Step S1, spray pyrolysis synthesis: yttrium nitrate, aluminum nitrate, and citric acid are dissolved in a mixed solvent of ethanol and water to obtain a precursor solution, and spray pyrolysis reaction is carried out under a nitrogen atmosphere, with nitrogen carrier gas, a flow rate of 25 L / min, an inlet temperature of 300°C, a reaction zone temperature of 1320°C, an atomization pressure of 0.3 MPa, and a residence time of 2 seconds to obtain spherical particles; wherein, in the precursor solution, yttrium nitrate is Y(NO3)3·6H2O with a concentration of 0.8 mol / L, aluminum nitrate is Al(NO3)3·9H2O with a concentration of 2.0 mol / L, and the concentration of citric acid is 1.2 mol / L, and the volume ratio of deionized water to ethanol in the solvent is 1:1;

[0070] Step S2, placing the spherical particles into a plasma reactor, introducing a mixture of hexafluoroethane and argon at a pressure of 18 Pa, a power of 280 W, and a temperature of 160° C. for 12 minutes to form a fluorinated layer; wherein the volume ratio of hexafluoroethane to argon in the mixture of hexafluoroethane and argon is 2:2.8;

[0071] Step S3: perfluorodecyltrimethoxysilane and hexane are mixed to obtain a mixed solution, triethylamine is added, and then the fluorinated spherical particles are added to the above solution, and the mixture is reacted at 35° C., magnetic stirring at 200 rpm, and a dry nitrogen atmosphere for 6 hours. Then, the mixture is centrifuged at 4000 rpm for 10 minutes, the particles are collected, and the particles are washed with hexane three times (10 ml / g particles each time) to remove the physically adsorbed perfluorodecyltrimethoxysilane, and vacuum dried at 120° C. for 1.5 hours to obtain the product. In step S3, the concentration of perfluorodecyltrimethoxysilane in the mixed solution is 2%, the amount of triethylamine added is 0.1% of the mixed solution, and the weight ratio of the fluorinated spherical particles to perfluorodecyltrimethoxysilane is 100:2.

[0072] The preparation method of the above-mentioned wear-resistant rare earth magnesium alloy composite material, in step b, prepares a transition layer: the transition layer raw materials include 25 parts of rare earth composite and 75 parts of magnesium yttrium alloy in parts by weight, which are mixed and prepared by surfacing welding, wherein the current is 130A, the scanning speed is 3.5mm / s, the powder feeding rate is 19g / min, and the gas is protected by a mixed gas of argon and hydrogen, the volume ratio of Ar to H2 is 97:3, and the flow rate is 14L / min; the rest is the same as Example 1.

[0073] Example 4

[0074] A wear-resistant rare earth magnesium alloy composite material comprises a magnesium alloy matrix layer, a transition layer, and a wear-resistant layer in sequence. The wear-resistant layer comprises 25 parts of modified tungsten carbide particles, 7 parts of rare earth composite, and 66 parts of nickel-based alloy powder in parts by weight; the rest is the same as in Example 1.

[0075] Comparative Example 1

[0076] A wear-resistant rare earth magnesium alloy composite material, wherein the modified tungsten carbide in the wear-resistant layer is replaced with ordinary commercially available tungsten carbide, and the rest is the same as in Example 1.

[0077] Comparative Example 2

[0078] A wear-resistant rare earth magnesium alloy composite material, wherein the modified tungsten carbide in the wear-resistant layer is replaced by ordinary commercially available tungsten carbide, the rare earth composite is replaced by commercially available yttrium oxide, and the rest is the same as in Example 1.

[0079] Comparative Example 3

[0080] A wear-resistant rare earth magnesium alloy composite material, wherein the rare earth composite is replaced with commercially available yttrium oxide, and the rest is the same as in Example 1.

[0081] Comparative Example 4

[0082] A method for preparing a wear-resistant rare earth magnesium alloy composite material. During the preparation process, the post-treatment step is annealing at 380° C. for 3 hours, and the rest is the same as in Example 1.

[0083] The wear resistance, corrosion resistance, hardness and mechanical properties of the material samples of Examples 1-4 and Comparative Examples 1-4 were tested respectively:

[0084] 1. Wear resistance: Wear resistance test: Dry abrasive wear test was conducted according to ASTM G65A, using ABT-3 abrasive wear testing machine, and the quartz sand particle size was 40-70 mesh.

[0085] 2. Corrosion resistance: Salt spray test. The test method is based on the national standard GB / T10125-2012 "Artificial atmosphere corrosion test salt spray test". The salt spray solution is 5% NaCl solution, pH 6.5-7.2, and the temperature is (35±1)°C. The test time is one month, and the corrosion rate (i.e., the percentage of mass loss) is calculated by the weight difference before and after.

[0086] 3. Hardness test: Use HR-150A Rockwell hardness tester with a load of 150 kg. Take 5 hardness points for each test sample and calculate the average value.

[0087] 4. Mechanical test: Tensile performance test is carried out according to GB / T16865-2013.

[0088] Table 1. Performance test results

[0089]

[0090]

[0091] As can be seen from the above table, the various properties of the rare earth magnesium alloy composite materials of Examples 1-4 are better than those of Comparative Examples 1-4, indicating that the composite materials of the present invention achieve improved wear resistance by modifying tungsten carbide and rare earth composites, and also have good corrosion resistance and mechanical properties, etc., and have good comprehensive performance. At the same time, the gradient annealing and shot peening processes of post-treatment further eliminate residual stress, reduce the source of corrosion cracks, and further improve mechanical properties and wear resistance and corrosion resistance. In Comparative Examples 1 and 2, the unmodified WC oxidizes and peels off, and the wear resistance is reduced. In Comparative Examples 2 and 3, ordinary commercially available yttrium oxide is used, the particles are easy to agglomerate, and there is no fluorocarbon protection, so the wear resistance and corrosion resistance are reduced. The post-treatment process of Comparative Example 4 leads to the production of brittle phases and residual stress, which reduces the mechanical properties and corrosion resistance.

[0092] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0093] Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A wear-resistant rare earth magnesium alloy composite material, characterized in that: The invention comprises a magnesium alloy matrix layer, a transition layer and a wear-resistant layer in sequence, wherein the wear-resistant layer comprises 20 to 25 parts by weight of modified tungsten carbide particles, 6 to 10 parts by weight of rare earth compound and 65 to 70 parts by weight of nickel-based alloy powder; The preparation method of the modified tungsten carbide particles comprises the following steps: Step 1: immerse the tungsten carbide powder in a mixed acid solution, ultrasonically treat it at 70-75°C for 25-35 minutes, and then wash and dry it; Step 2: Place the activated tungsten carbide into a fluidized bed reactor, evacuate to 10-2Pa, introduce reaction gas, which is titanium tetrachloride, nitrogen and hydrogen, and deposit at 890-910°C for 40-50 minutes to obtain tungsten carbide composite particles; Step 3: The tungsten carbide composite particles are subjected to vacuum degassing pretreatment at a temperature of 240-260°C for 25-35 minutes under vacuum conditions, and then filled with argon to normal pressure, followed by introduction of argon-hydrogen mixed gas, at a power of 2.8-3.2kW and a temperature of 290-310°C, for plasma reduction for 35-45 minutes.

2. The wear-resistant rare earth magnesium alloy composite material according to claim 1, characterized in that: In step 1, the mixed acid solution includes phosphoric acid, nitric acid, and deionized water in a volume ratio of 12-16:8-12:70-80, the phosphoric acid concentration is 85%, the nitric acid concentration is 65%, and the weight volume ratio of the tungsten carbide powder to the mixed acid solution is 1g:7-9ml.

3. The wear-resistant rare earth magnesium alloy composite material according to claim 1, characterized in that: In step 2, the flow rates of the reaction gases are: titanium tetrachloride 48-52 ml / min, nitrogen 550-600 ml / min, and hydrogen 290-310 ml / min.

4. The wear-resistant rare earth magnesium alloy composite material according to claim 1, characterized in that: In step 3, the volume percentage of hydrogen in the argon-hydrogen mixed gas is 3%.

5. The wear-resistant rare earth magnesium alloy composite material according to claim 1, characterized in that: The method for preparing the rare earth composite comprises the following steps: Step S1, spray pyrolysis synthesis: yttrium nitrate, aluminum nitrate, and citric acid are dissolved in a mixed solvent of ethanol and water to obtain a precursor solution, and spray pyrolysis reaction is carried out under a nitrogen atmosphere with nitrogen carrier gas at a flow rate of 25 to 30 L / min, an inlet temperature of 300° C., a reaction zone temperature of 1280-1320° C., an atomization pressure of 0.3 MPa, and a residence time of 2 to 2.5 seconds to obtain spherical particles; Step S2, placing the spherical particles into a plasma reactor, introducing a mixed gas of hexafluoroethane and argon at a pressure of 18-22 Pa, a power of 280-320 W, and a temperature of 140-160° C. for 8-12 minutes to form a fluorinated layer; Step S3, perfluorodecyltrimethoxysilane and hexane are mixed to obtain a mixed solution, triethylamine is added, and then the fluorinated spherical particles are added to the above solution, reacted at 35-45° C. in a dry nitrogen atmosphere for 4-6 hours, and post-treated to obtain the product.

6. The wear-resistant rare earth magnesium alloy composite material according to claim 5, characterized in that: In step S1, in the precursor solution, yttrium nitrate is Y(NO3)3·6H2O with a concentration of 0.8 mol / L, aluminum nitrate is Al(NO3)3·9H2O with a concentration of 2.0 mol / L, citric acid concentration is 1.2 mol / L, and the volume ratio of deionized water and ethanol in the solvent is 1:

1.

7. The wear-resistant rare earth magnesium alloy composite material according to claim 5, characterized in that: In step S2, the volume ratio of hexafluoroethane to argon in the mixed gas of hexafluoroethane and argon is 2:2.8-3.

2.

8. The wear-resistant rare earth magnesium alloy composite material according to claim 5, characterized in that: In step S3, the concentration of perfluorodecyltrimethoxysilane in the mixed solution is 1% to 2%, the amount of triethylamine added is 0.1% of the mixed solution, and the weight ratio of the fluorinated spherical particles to perfluorodecyltrimethoxysilane is 100:1-2.

9. The method for preparing the wear-resistant rare earth magnesium alloy composite material according to any one of claims 1 to 8, characterized in that: The wear-resistant layer preparation method comprises the following steps: mixing the wear-resistant layer raw materials, and then performing cladding under the conditions of a laser power of 2.0-2.8 kW, a scanning speed of 3.3-3.7 mm / s, and argon protection.

10. The method for preparing the wear-resistant rare earth magnesium alloy composite material according to claim 8, characterized in that: The transition layer raw materials include 25 to 35 parts of rare earth compound and 65 to 75 parts of magnesium yttrium alloy by weight, and are prepared by surfacing welding with a current of 130 to 150 A, a scanning speed of 2.5 to 3.5 mm / s, a powder feeding rate of 16 to 19 g / min, and are carried out under the protection of a mixed gas of argon and hydrogen, with a volume ratio of Ar to H2 of 97:3 and a flow rate of 10 to 14 L / min.